Differentiated Learning-Based Interactive Multimedia: An Effort to Improve Learning Outcomes on the Topic of Ecosystems for Grade V Elementary School Students - Astri Muliawati; Erwin Putera Permana; Nurita Primasatya (Alifbata : Jurnal Pendidikan Dasar, 2026)
The implementation of the Merdeka Curriculum requires learning processes that accommodate students’ diverse learning needs. This study aimed to develop differentiated learning-based interactive multimedia on ecosystem material and to examine its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 28 fifth-grade students of SDN Lirboyo 2 Kediri City, involved in both limited-scale and large-scale trials. Data were collected through observations, interviews, questionnaires, validation sheets, and pretest-posttest assessments, and were analyzed using descriptive quantitative techniques with percentage scores and N-Gain analysis. The results indicated that the developed multimedia achieved a validity score of 96% (very valid), a practicality score of 90% (very practical), and an N-Gain score of 0.84 (high). Therefore, the differentiated learning-based interactive multimedia was considered valid, practical, and effective in improving students’ learning outcomes on ecosystem material.